THE MAIN FORMS OF HIGHER QUALIFIED STAFF TRAINING IN UKRAINE IN 1945-1957 - Reheilo, Irina (Continuing Professional Education: Theory and Practice, 2019)
Under the conditions of Ukraine’s induction into European higher education area and European Research Area critical comprehension of domestic experience of staff training through postgraduate and doctoral studies as well as account of achievements and failings of the past contributes to successful forming of national education system. The historical period of 1945-1957 is characterized by tense search of new ways and forms of higher qualified staff training. The chronological limits are determined by post-war period (1945) conditions of national economy renewal and by the Central Committee of the Communist Party and the Council of Ministers decisions which abolished the staff training through doctoral studies. The article grounds that the main forms of qualified research and research pedagogical staff training were: sending the most perspective specialists for a two-year postgraduate and doctoral studies in order to prepare and defend dissertations; establishing lecture instructor vacancies to prepare and defend dissertations while completing the lecture instructor duties under professor’s supervision; establishing in universities one-year postgraduate study in order to help university and school staff who need the release from their basic job to finish their research and defend their dissertation; introduction of candidate for a degree institute for people who prepare their dissertation while working at their basic job; establishing three-month creative vacation for completing candidate’s dissertation and six-month creative vacation for completing doctor’s dissertation. During the renewal process of the system of staff training through postgraduate and doctoral studies in Ukraine in 1945-1957 and introduction of new forms the growth of quantitative and high-quality indexes was observed.